2019
DOI: 10.1002/adfm.201906833
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Photonic Materials via Monitoring Step‐Growth Polymerization Kinetics by Structural Colors

Abstract: The functional and responsive properties of elastomeric materials highly depend on crosslink density and molecular weight between crosslinks. However, tedious analytical steps are needed to obtain polymer network structure–property relationships. In this article, an in situ structure–property characterization method is reported by monitoring the structural color change in a photonic elastomeric material. The photonic materials are prepared in a two‐step polymerization process. First, linear chain extension occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…The CLCE is made using a two‐step crosslinking involving a base‐catalyzed thiol‐acrylate reaction and a light‐induced free radical polymerization reaction reported previously. [ 36–38 ] The CLC mixture is composed of 6 components ( Figure A). Monomer 1 is a liquid crystal diacrylate monomer and monomer 2 is a chiral dopant that induces the formation of the cholesteric liquid crystal phase.…”
Section: Resultsmentioning
confidence: 99%
“…The CLCE is made using a two‐step crosslinking involving a base‐catalyzed thiol‐acrylate reaction and a light‐induced free radical polymerization reaction reported previously. [ 36–38 ] The CLC mixture is composed of 6 components ( Figure A). Monomer 1 is a liquid crystal diacrylate monomer and monomer 2 is a chiral dopant that induces the formation of the cholesteric liquid crystal phase.…”
Section: Resultsmentioning
confidence: 99%
“…[85,89,179] Increasingly, researchers are introducing other functionalities to photonic or plasmonic polymers, drawing from diverse areas of material science: examples include supramolecular selfhealing, [256] shape memory, [245,[250][251][252]257] and tunable moduli. [178] These designer materials could be particularly useful in areas such as soft robotics or electronic skins, [63,258,259] where polymeric components with bright, tunable color and the ability to self-repair for an improved product lifetime are highly desirable. It is certain that advances in structurally colored mechanochromic polymers such as these will drive the development of novel optical technologies, solving challenges across the fields of communications, optics, and sensing.…”
Section: Discussionmentioning
confidence: 99%
“…This result was attributed to the increase in surface roughness of the film that was caused by the roughness of the indenter. Gravure printing, another type of scalable roll‐feed printing, has also been used to produce patterned, stimuli‐responsive photonic materials, [ 178 ] and could be applied to mechanochromic LC materials in the future. In addition to thin films, microspheres of CLC elastomers can be produced by polymerizing emulsion droplets containing monomeric mesogens, with the LC ordering induced from the oil–water interface.…”
Section: Bottom‐up Approaches: Creating Structural Coloration Throughmentioning
confidence: 99%
“…Similar RPPs in response to water or other stimulus can also be printed on cholesteric liquid crystals. [ 77–89 ] For example, Schenning's group [ 83,84 ] demonstrated that RPPs can be prepared by selective cross‐linking the cholesteric photonic film, which show reversible color under solvent or different temperature. Despite these successes, most of the fabricated RPPs show simple change in color contrast in response to the solvents.…”
Section: Introductionmentioning
confidence: 99%